The Antecedents Of Organizational Performance With Corporate Carbon Management Strategy As Moderation - Whittleliang Hakki , Tandry; Akwila, Karvicha; Jurjanta, Priccilya (Dinasti International Journal of Economics, Finance & Accounting, 2024)
In recent years, the rapid growth of civilization and industrialization has had a significant impact on environmental sustainability. The rise of human revolution and technological developments aimed at making people's lives more comfortable have indirectly contributed to environmental degradation, thus causing adverse effects on human health. Excessive exploitation of natural resources has drawn public attention to environmental issues both at national and international levels. This study aims to examine the effect of Green Supply Chain Management, Green Intellectual Capital, and Competitive Business Strategy on organizational performance, and to examine whether Corporate Carbon Management Strategy can strengthen the effect of Green Supply Chain Management, Green Intellectual Capital, and Competitive Business Strategy on organizational performance. The type of data used in this study is primary data in the form of financial reports of companies that are used as samples. The research method used in this study is a quantitative research method. The sample was selected using the purposive sampling method. For hypothesis testing, this study uses multiple linear regression analysis. Based on the results of this study, it shows that Green Supply Chain Management and Competitive Business Strategy have an effect on Organizational Performance, but Green Intellectual Capital, have not effect on Organizational Performance. Carbon Management Strategy strengthens the influence of Green Supply Chain Management and Competitive Business Strategy on Organizational Performance and Carbon Management Strategy does not strengthen the influence of Green Intellectual Capital Strategy on Organizational Performance